Receptor tyrosine kinase–GPCR signal complexes. (1st December 2003) - Pyne, N.J.; Waters, C.; Moughal, N.A.; Sambi, B.S.; Pyne, S.
Abstract : The formation of complexes between growth factor receptors and members of a family of G-protein-coupled receptors whose natural ligands are S1P (sphingosine 1-phosphate) and LPA (lysophosphatidic acid) represents a new signalling entity. This receptor complex allows for integrated signalling in response to growth factor and/or S1P/LPA and provides a mechanism for more efficient activation (due to integrated close-proximity signalling from both receptor classes) of the p42/p44 MAPK (mitogen-activated protein kinase) pathway. This article provides information on the molecular events at the interface between receptor tyrosine kinases and S1P/LPA receptors. Examples include the PDGF (platelet-derived growth factor)-induced tyrosine phosphorylation of Gi α, released upon S1P1 receptor activation, which is required for initiation of the p42/p44 MAPK pathway. Critical to this event is the formation of endocytic vesicles containing functionally active PDGFβ receptor–S1P1 receptor complexes, which are internalized and relocated with components of the p42/p44 MAPK pathway. We also report examples of cross-talk signal integration between the Trk A (tropomyosin receptor kinase A) receptor and the LPA1 receptor in terms of the NGF (nerve growth factor)-dependent regulation of the p42/p44 MAPK pathway. NGF induces recruitment of the LPA1 receptor to the nucleus (delivery might be Trk A-dependent), whereupon the LPA1 receptor may govern gene expression via novel nuclear signalling processes.